PERLINDUNGAN DAN KEPASTIAN HUKUM BAGI PENGENDALI DATA PRIBADI DI MASA DEPAN - Firdaus, Febrian Hilmi (Faculty of Law, Universitas Diponegoro, 2024)
The enactment of Law Number 27 of 2022 on Personal Data Protection (PDP Law) offers new hope for safeguarding personal data. However, vague regulations and the absence of implementing rules create legal uncertainty for personal data controllers, threatening their professionalism in the future. This study aims to explore the legal protection and certainty for personal data controllers based on legal norms, principles, and theories. The research employs a normative-juridical legal method with a statutory and conceptual approach. Findings indicate that personal data controllers require concrete legal protection and implementing regulations to ensure balance among legal subjects. This study recommends regulatory developments to guarantee predictability and fairness for personal data controllers.